New Results in Numerical and Experimental Fluid Mechanics IX Contributions to the 18th STAB/DGLR Symposium, Stuttgart, Germany, 2012 - Dillmann, Andreas; Heller, Gerd; Krämer, Ewald; Kreplin, Hans-Peter; Nitsche, Wolfgang; Rist, Ulrich (Notes on Numerical Fluid Mechanics and Multidisciplinary Design, 2014)
This book presents contributions to the 18th biannual symposium of the German Aerospace Aerodynamics Association (STAB). The individual chapters reflect ongoing research conducted by the STAB members in the field of numerical and experimental fluid mechanics and aerodynamics, mainly for (but not limited to) aerospace applications, and cover both nationally and EC-funded projects. By addressing a number of essential research subjects, together with their related physical and mathematics fundamentals, the book provides readers with a comprehensive overview of the current research work in the field, as well as its main challenges and new directions. Current work on e.g. high aspect-ratio and low aspect-ratio wings, bluff bodies, laminar flow control and transition, active flow control, hypersonic flows, aeroelasticity, aeroacoustics and biofluid mechanics is exhaustively discussed here.  .